The Relations Between Ottoman State and Egypt (1863 – 1879) (Journal of the College of Education for Women, 2019)
Facts and information contained showing in axes Find Egyptian Ottoman relations(1863-1879), has gone through stages varying between tides, has witnessed the KhediveIsmail three sultans Ottomans were Abdul Aziz Murad V, Abdul Hamid II, and since theKhedive Ismail to judge sought to expand independence Egypt access to many privileges ofthe sovereign on Egypt Ottoman Empire, in order to reach the country to independence, hasbeen chosen by the payment of money and gifts to gain independence, without resorting toarms, and from this point of Khedive make a lot of money to get the privileges, the state ofthe Ottoman were not to issue Farmans but against the huge amounts of money, and as aresult of that policy got Furman in 1866, under which justice and inherit the throne system,and Furman in private in 1867 by granting the title of Khedive, but the efforts of the KhediveIsmail to show the appearance of the independent King was a cause of the Egyptian Ottomancrisis between 1869 and 1872 is that the Khedive Ismail ambitions that one has made himseek to get closer to the government of Astana for more than Farmans, that managed to get afirman Whole in 1873, and which culminated in pursuit of the Khedive to gain fullindependence, the culmination of a final, and made under its association with the Ottomanstate as it were non-existent.It is clear from Farmans obtained by Khedive Ismail of Egypt to link the Ottomanstate became nominally, is no longer the Ottoman state the right to intervene in and appoint toEgypt, as well as Egypt's independence in economic terms from the Ottoman Empire.On the other hand, the Khedive Ismail policy wrong and borrowed huge amounts ofmoney from foreign banks, European countries pushed for intervention in the affairs of Egyptduring his reign, until it came out that those countries have begun fear of non-payment ofdebts, so pressed by Britain and France at the Porte to isolate Alkhdioa Ismail was to do so inthe twenty-sixth of June 1879